Measuring the job stress of the employed population: The case of labor market in Cali-Colombia - Bilver Adrián Astorquiza Bustos; Maribel Castillo Caicedo; Alina Gomez Mejia (Revista de Métodos Cuantitativos para la Economía y la Empresa, 2018)
From Survey of Employment and Quality of Life, the hypothesis of job stress is analyzed for individuals who meet the condition of being employed and being between the ages of 16 years old (the age at which is assumed that they have completed median education) and 62 years old (retirement age for men) in Cali-Colombia; resulting a sub-sample of 10,158 observations. As a theoretical foundation, we use a variant of the leisure-consumption model, in which the appearance of stress is based on the imbalance of the equilibrium condition. The results suggest that, in effect, there are signs of job stress in the labor market in Cali. As a complementary activity, we estimated an econometric model to know the profile of the individuals who present a greater probability of being stressed based on three components: sociodemographic, health and labor characteristics of the individual. Thus, working more than 48 hours a week, not having a work premium, reducing a low proportion of income to leisure activities, being a woman, among other factors are associated with a high probability of job stress.
Keywords: J21; J28; C25; J24; 330; labor force; Job stress; multinomial models; social choice